Visual efficiency among teenaged athletes and non-athletes - Omar, Rokiah; Yau, Meng Kuan; Zuhairi, Nurul Atikah; Abd Manan, Faudziah; Knight, Victor Feizal (Press of International Journal of Ophthalmology, 2017)
AIM To compare visual efficiency, specifically accom-modation, vergence, and oculomotor functions among athletes and non-athletes.